Vasorelaxant effect of isoquinoline derivatives from two species of Popowia perakensis and Phaeanthus crassipetalus on rat aortic artery - Awang, K.; Zaima, K.; Takeyama, Y.; Koga, I.; Saito, A.; Tamamoto, H.; Syed Abd. Azziz, S.S.; Mukhtar, M.R.; Hadi, A.H.; Morita, H. (Springer Verlag, 2012)
Five bisbenzyl isoquinolines (1-5), three benzyl isoquinolines (6-8), four isoquinoline alkaloids (9-12), and two unclassified compounds (13 and 14) from Popowia perakensis and Phaeanthus crassipetalus were evaluated for their vasorelaxant effect on rat aortic arteries. In aortic rings pre-contracted with phenylephrine (PE, 0.3 μM), some of the bisbenzyl isoquinoline alkaloids, benzyl isoquinoline alkaloids, and isoquinoline alkaloids showed clearly vasorelaxant effects at 30 μM. The action of (-)-limacine (4) was deduced to be mediated through the increased release of NO from endothelial cells, and that of pecrassipine A (7) and backebergine (12) partly mediated by NO release. Further, the action of pecrassipine A (7) and backebergine (12) may be attributed to their inhibition of the voltage-dependent Ca(2+) channel and receptor-operated Ca(2+) channel.